Kingdom of the Netherlands : Netherlands; 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of the Netherlands; Netherlands. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The 2007 Article IV Consultation with the Kingdom of the Netherlands explains fiscal policy and financial sector issues. Improvements in the macroeconomic and business environments and technological innovation have contributed positively to Dutch competitiveness. Executive Directors emphasized that continued improvement in the underlying fiscal position requires tight spending control. They recommended that the authorities implement offsetting expenditure-reducing measures. They also commended the risk-oriented, cross-sectoral approach to financial sector supervision, pointing out that, in many respects, the design and implementation of supervision in the Netherlands are international best practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet